Evidence for nonlinear development of magnetohydrodynamic scale intermittency in the inner heliosphere - Greco, A. (2012)
The formation of coherent structures in turbulence is a signature of a developing cascade and therefore might be observable by analyzing inner heliospheric solar wind turbulence. To test this idea, data from the Helios 2 mission, for six streams of solar wind at different heliocentric distances and of different velocities, were subjected to statistical analysis using the partial variance of increments (PVI) approach. We see a clear increase of the PVI distribution function versus solar wind age for higher PVI cutoff, indicating development of non-Gaussian coherent structures. The plausibility of this interpretation is confirmed by a similar behavior observed in two-dimensional magnetohydrodynamics simulation data at corresponding dimensionless nonlinear times. © 2012. The American Astronomical Society. All rights reserved.